The Mediating Role of Wara’ in Green Halal Purchase Behavior among Generation Z - Astuti, Andi; Razak, Syaparuddin; Farida, Ida (Universitas Airlangga, 2025)
This study aims to analyze the mediating role of wara’ in linking Islamic ethics, religious norms, and environmental awareness to green halal purchase behavior among Generation Z consumers. A survey was conducted with 157 Muslim Gen Z respondents in South Sulawesi using convenience sampling and a five-point Likert scale. Data were analyzed using SEM-PLS (SmartPLS 4) through measurement and structural model assessments. The findings indicate that Islamic ethics significantly influence the formation of wara’, and wara’ serves as a mediator that strengthens green halal purchase behavior. Religious norms directly affect consumer behavior, while environmental awareness reinforces ethical consumption orientation. These results demonstrate that the internalization of moral and spiritual values contributes to more consistent sustainable consumption behavior. The study implies the importance of halal literacy programs, value-based education, and ethical marketing strategies to cultivate responsible, sustainability-oriented consumer behavior aligned with Islamic principles.